2007
DOI: 10.1111/j.1472-765x.2007.02182.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different growth media for the recovery of the species of Alicyclobacillus

Abstract: Aims:  Five different isolation media, namely potato dextrose agar (PDA), orange serum agar (OSA), K agar, yeast–starch–glucose agar and Bacillus acidocaldarius medium were evaluated for the recovery of Alicyclobacillus spp. from inoculated diluted and undiluted fruit‐juice concentrates. Methods and Results:  Plates of PDA (pH 3·7), spread with vegetative cells (3·9 × 106 CFU ml−1) of Alicyclobacillus acidoterrestris from single‐strength pear juice, recovered 2·9 × 106 CFU ml−1 after 5 days at 50°C (74% recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…Potato dextrose agar (PDA) (Merck) at pH 3·7 was adjusted with 1 mol l −1 H 2 SO 4 (Chang and Kang 2004; Witthuhn et al. 2007), and the spread plating method was used to recover Alicyclobacillus from the samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Potato dextrose agar (PDA) (Merck) at pH 3·7 was adjusted with 1 mol l −1 H 2 SO 4 (Chang and Kang 2004; Witthuhn et al. 2007), and the spread plating method was used to recover Alicyclobacillus from the samples.…”
Section: Methodsmentioning
confidence: 99%
“…Potato dextrose agar (PDA) (Merck) at pH 3AE7 was adjusted with 1 mol l )1 H 2 SO 4 (Chang and Kang 2004;Witthuhn et al 2007), and the spread plating method was used to recover Alicyclobacillus from the samples. Samples that did not receive a heat-shock treatment prior to plating were enumerated as vegetative cells, as it has been reported that Alicyclobacillus endospores require a heatshock treatment to ensure germination (Pettipher et al 1997;Yokota et al 2007).…”
Section: Enumerationmentioning
confidence: 99%
“…When Witthuhn (2007) evaluated the effect of Potato Dextrose Agar (PDA), Orange Serum Agar (OSA), Bacillus acidocaldarius medium (BAM), YSG and K agar media upon the growth of alicyclobacillus, the author reported that PDA and OSA media provided the best cell recovery. K agar, on the other hand, failed to recover A. acidoterrestris cells inoculated in concentrated pear juice, and failed to recover A. pomorum cells inoculated after 80°C thermal treatment for 10 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…A. acidoterrestris K47 (Witthuhn et al, 2007), a strain isolated from grape juice concentrate and A. acidoterrestris FB2 (Groenewald et al, 2008) isolated from pear juice concentrate were used in this study. Potato dextrose agar (PDA) (Biolab, Biolab Diagnostics, Midrand, SA) adjusted with tartaric acid (1N) (Saarchem, Krugersdorp, South Africa) to a final pH of 4 was used as a culture medium (Witthuhn et al, 2007).…”
Section: Bacterial Strainsmentioning
confidence: 99%